NEW OPPORTUNITIES OF CROWDSOURCING AND CROWDFUNDING IN BUSINESS - Xusanboyeva Tursunoy Muxammadqasimdjanovna (Ecomind Press, 2025)
This article analyzes the role of crowdsourcing and crowdfunding in modern business, their importance in the development of entrepreneurial activity, and the use of these technologies in Uzbekistan. Through crowdsourcing, companies have the opportunity to attract ideas and skills from a wide audience, which serves to improve products and services. Crowdfunding is an alternative to traditional methods of financing projects and is carried out by collecting small amounts of funds from the general public. The article also discusses the prospects for the development of these technologies in Uzbekistan and the advantages of their use.
Keywords: Crowdsourcing, crowdfunding, collective financing, innovative business, digital economy, entrepreneurship, Uzbekistan, startups, financial technologies, public idea generation.